A subjective refraction-based assessment of image quality metric - Iskander, D. Robert (Photonics Letters of Poland, 2011)
Tools for quantifying image quality should be bench-marked against subjective human assessment. It is expected that image quality metrics (IQMs) that are based on a human visual system should closely correlate with an observer’s perception of vision quality. Performances of a range of popular IQMs were evaluated using subjective and objective measures of optimal refraction from 120 eyes. An optimization algorithm was devised in which objective refraction corresponding to the peak of a given IQM was sought. That optimized objective refraction was then correlated with the corresponding subjective refraction. The results show that although most IQMs result in a similar performance for defocus, those which only use the second order statistical information do not correlate well with a subjective assessment of image quality. Full Text: PDF References: A.J. Ahumada, Jr., SID International Symposium Digest of Technical Papers 24, 305 (1993). A.M. Eskicioglu, P.S. Fisher, "Image quality measures and their performance", IEEE Trans. Commun. 43, 2959 (1995). [CrossRef] M. Antonini, M. Barlaud, P. Mathieu, I. Daubechies, "Image coding using wavelet transform", IEEE Trans. Image. Proc. 1, 205 (1992). [CrossRef] Z. Wang, A.C. Bovik, L.Lu, "Video quality assessment using structural distortion measurement", Proc. IEEE ICASSP, 3313 (2002). [CrossRef] D.J. Granrath, "The role of human visual models in image processing", Proc. IEEE 69, 552 (1981). [CrossRef] Z. Wang, A.C. Bovik, "A universal image quality index", IEEE Signal Process. Lett. 9, 81 (2002). [CrossRef] Z. Wang, A.C. Bovik, H.R. Sheikh, E.P. Simoncelli, "Image quality assessment: from error visibility to structural similarity", IEEE Trans. Image Proc. 13, 600 (2004).[CrossRef] H.R. Sheikh, A.C. Bovik, "Image information and visual quality", IEEE Trans Image Process. 15, 430 (2006). [CrossRef] X. Cheng, A. Bradley, L.N. Thibos, J. Vis. "Dalton’s Jungle: a video game for assessing color anomalies in children’s vision", 4, 310 (2004). [CrossRef] L. Chen, B. Singer, A. Guirao, J. Porter, D.R. Williams, "Visual Agnosia, 2nd Ed.", Optom. Vis. Sci. 82, 358 (2005). [CrossRef] J.D. Marsack, L.N. Thibos, R.A. Applegate, "Metrics of optical quality derived from wave aberrations predict visual performance", J. Vis. 4, 322 (2004). [CrossRef] A. Guirao, D.R. Williams, "A Method to Predict Refractive Errors from Wave Aberration Data", Optom. Vis. Sci. 80, 36 (2003). [CrossRef] I.L. Bailey, J.E. Lovie, "he design and use of a new near-vision chart", Am. J. Optom. Physiol. Opt. 57, 378 (1980). [DirectLink] American National Standards for Ophthalmics. Methods for reporting optical aberrations of eyes. ANSI Z80.28 (2004). [DirectLink] D.A. Silverstein, J.E. Farrell, "The relationship between image fidelity and image quality ", Proc. IEEE ICASSP, 881 (1996). [CrossRef] L.N. Thibos, X. Hong, A. Bradley, R.A. Applegate, "Accuracy and precision of objective refraction from wavefront aberrations", J. Vis. 4, 329 (2004). [CrossRef] D.R. Iskander, M.J. Collins, B. Davis, R. Franklin, "Objective refraction from monochromatic wavefront aberrations via Zernike power polynomials", Ophthal. Physiol. Opt. 27, 245 (2007). [CrossRef] J. Nam, L.N. Thibos, D.R. Iskander, "Zernike radial slope polynomials for wavefront reconstruction and refraction", J. Opt. Soc. Am. A Opt. Image. Sci. Vis. 26, 1035 (2009). [CrossRef] J. Nam, L.N. Thibos, D.R. Iskander, "Describing ocular aberrations with wavefront vergence maps", Clin. Exp. Optom. 92, 194 (2009). [CrossRef] R.K. Maloney, S.J. Bogan, G.O. 3rd Waring, "Determination of corneal image-forming properties from corneal topography.", Am. J. Ophthalmol. 115, 31 (1993). [CrossRef] O. T. Salmon, R.W. West, W. Gasser, T. Kenmore, "Measurement of Refractive Errors in Young Myopes Using the COAS Shack-Hartmann Aberrometer", Optom. Vis. Sci. 80, 6 (2003). [CrossRef] R.T. Hennessy, "Instrument myopia", J. Opt. Soc. Am. 65, 1114 (1975).[CrossRef] W.N. Charman, "Wavefront Aberration of the Eye: A Review", Optom Vis Sci. 68, 574 (1991). [CrossRef] D.A. Atchison, "Recent advances in representation of monochromatic aberrations of human eyes", Clin Exp Optom. 87, 138 (2004). [CrossRef] M J. Collins, T. Buehren, D.R. Iskander, "Retinal image quality, reading and myopia", Vis. Res. 46, 196 (2006).[CrossRef] T. Buehren, M.J. Collins, "Accommodation stimulus?response function and retinal image quality", Vis. Res. 46, 1633 (2006). [CrossRef] A. Guirao, J. Porter, D.R. Williams, I.G. Cox, "Calculated impact of higher-order monochromatic aberrations on retinal image quality in a population of human eyes: erratum", J. Opt. Soc. Am. A Opt. Image. Sci. Vis. 19, 620 (2002). [CrossRef]